Sit-stand desks to reduce sedentary behaviour in 9- to 10-year-olds: the Stand Out in Class pilot cluster RCT - Stacy Clemes; Daniel Bingham; Natalie Pearson; Yu-Ling Chen; Charlotte Edwardson; Rosemary McEachan; Keith Tolfrey; Lorraine Cale; Gerry Richardson; Michael Fray; James Altunkaya; Stephan Bandelow; et al. (2020)
Background Sedentary behaviour (sitting) is a highly prevalent negative health behaviour, with individuals of all ages exposed to environments that promote prolonged sitting. The school classroom represents an ideal setting for environmental change through the provision of sit–stand desks. Objectives The aim of this study was to undertake a pilot cluster randomised controlled trial of the introduction of sit–stand desks in primary school classrooms, to inform a definitive trial. Objectives included providing information on school and participant recruitment and retention, acceptability of the intervention, and outcome measures. A preliminary estimate of the intervention’s effectiveness on the proposed primary outcome (change in weekday sitting time) for inclusion in a definitive trial was calculated, along with a preliminary assessment of potential cost-effectiveness. A full process evaluation was also undertaken. Design A two-armed pilot cluster randomised controlled trial with economic and qualitative evaluations. Schools were randomised on a 1 : 1 basis to the intervention (n = 4) or control (n = 4) trial arms. Setting Primary schools in Bradford, West Yorkshire, UK. Participants Children in Year 5 (i.e. aged 9–10 years). Intervention Six sit–stand desks replaced three standard desks (sitting six children) in the intervention classrooms for 4.5 months. Teachers were encouraged to ensure that all pupils were exposed to the sit–stand desks for at least 1 hour per day, on average, using a rotation system. Schools assigned to the control arm continued with their usual practice. Main outcome measures Trial feasibility outcomes included school and participant recruitment and attrition, acceptability of the intervention, and acceptability of and compliance with the proposed outcome measures [including weekday sitting measured using activPAL™ (PAL Technologies Ltd, Glasgow, UK) accelerometers, physical activity, adiposity, blood pressure, cognitive function, musculoskeletal comfort, academic progress, engagement and behaviour]. Results Thirty-three per cent of schools approached and 75% (n = 176) of eligible children took part. At the 7-month follow-up, retention rates were 100% for schools and 97% for children. Outcome measure completion rates ranged from 63% to 97%. A preliminary estimate of intervention effectiveness, from a weighted linear regression model (adjusting for baseline sitting time and wear time) revealed a mean difference in change in sitting of –30.6 minutes per day (95% confidence interval –56.42 to –4.84 minutes per day) between the intervention and control trial arms. The process evaluation revealed that the intervention, recruitment and evaluation procedures were acceptable to teachers and children, with the exception of minor issues around activPAL attachment. A preliminary within-trial economic analysis revealed no difference between intervention and control trial arms in health and education resource use or outcomes. Long-term modelling estimated an unadjusted incremental cost-effectiveness ratio of Stand Out in Class of £78,986 per quality-adjusted life-year gained. Conclusion This study has provided evidence of the acceptability and feasibility of the Stand Out in Class intervention and evaluation methods. Preliminary evidence suggests that the intervention may have a positive direction of effect on weekday sitting time, which warrants testing in a full cluster randomised controlled trial. Lessons learnt from this trial will inform the planning of a definitive trial. Trial registration Current Controlled Trials ISRCTN12915848. Funding This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 8, No. 8. See the NIHR Journals Library website for further project information.